Solid-phase sintered silicon carbide ceramic and preparation method thereof
By optimizing the raw material formula and sintering process of silicon carbide ceramics, the problem of overgrowth of grain during solid phase sintering is solved, and the fracture toughness and mechanical properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411683820.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
Prepared by solid-phase sintering of silicon carbide ceramics is prone to overgrowth of grains at high temperatures, resulting in uneven grain size distribution and reducing the fracture toughness and mechanical properties of the material.
The formula is adopted with a mass percentage of 86.5-92.5% silicon carbide powder, 3-6% carbon source additive, 0.2-1% boron source additive, 2-5% composite additive and 2-5% binder. , α-silicon carbide is modified by fluidized bed chemical vapor deposition method, and mixed with β-silicon carbide, combined with spray drying granulation, isostatic pressing and segmented sintering, optimize grain size distribution and grain boundary structure .
It significantly improves the fracture toughness and mechanical properties of silicon carbide ceramics, reduces grain overgrowth, and improves the density and high-temperature performance of the material.
Smart Images

Figure BDA0005148971300000051 
Figure BDA0005148971300000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon carbide ceramics, and more specifically, to a solid-phase sintered silicon carbide ceramic and a preparation method thereof. Background Art
[0002] With the continuous advancement of industrial technology, the demand for high-temperature refractory materials is growing, especially in the fields of metallurgy, petrochemicals, aerospace, energy and electronics, where high-temperature refractory materials play a vital role. Silicon carbide (SiC) ceramics have become an important choice in the field of high-temperature refractory materials due to their high strength, high hardness, excellent high-temperature performance, wear resistance and corrosion resistance, and their ability to maintain stable structure and performance under high-temperature environments, especially in high-temperature thermal management and high-temperature reaction heat exchange. It has a wide range of application potential and value.
[0003] Depending on the raw material formula, molding process and sintering parameters of silicon carbide ceramics, the density of silicon carbide ceramics is generally 2.5-3.2g / cm 3 Generally speaking, the higher the density of silicon carbide ceramics, the higher the density of silicon carbide ceramics, the more uniform the structure, the higher the mechanical properties and hardness. Since silicon carbide is covalently bonded, the diffusion rate during sintering is low and it is difficult to sinter densely under normal pressure. Therefore, the current preparation methods of silicon carbide ceramics mainly include solid phase sintering and liquid phase sintering.
[0004] Among them, solid-phase sintering uses boron and carbon as sintering aids and achieves dense sintering through solid-phase diffusion. The amount of sintering aids used is much less than that used in liquid-phase sintering, and no liquid phase is produced during the sintering process, so silicon carbide ceramics with higher strength and high-temperature resistance can be obtained.
[0005] With respect to the above-mentioned related technologies, the inventors found that although the solid-phase sintering method for preparing silicon carbide ceramics can maintain a high degree of cleanliness and avoid defects such as pores and cracks caused by liquid-phase sintering, during the solid-phase sintering process, the grains are prone to overgrowth at high temperatures, resulting in uneven grain size distribution. The fracture mode during fracture is intergranular fracture, that is, the crack extends along the grain boundary, rather than transgranular fracture that passes through the interior of the grain when the crack extends. This makes the overall fracture toughness and mechanical properties of the material relatively low. Summary of the invention
[0006] In order to improve the fracture toughness and mechanical properties of silicon carbide ceramics prepared by solid phase sintering, the present application provides a solid phase sintered silicon carbide ceramic and a preparation method thereof.
[0007] In a first aspect, the present application provides a solid phase sintered silicon carbide ceramic, which adopts the following technical solution: A solid-phase sintered silicon carbide ceramic, wherein the raw materials include, by mass percentage, 86.5-92.5% of silicon carbide powder, 3-6% of a carbon source additive, 0.2-1% of a boron source additive, 2-5% of a composite additive and 2-5% of a binder; The silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:(4.5-5); The composite auxiliary agent includes zirconium chloride and yttrium chloride in a mass ratio of (1-5):1.
[0008] By adopting the above technical solution, α-silicon carbide and β-silicon carbide have different crystal structures and particle size distributions. Mixing them in a suitable ratio can optimize the grain size distribution of the ceramic material, avoid performance defects caused by a single grain size that is too large or too small, and reduce stress concentration points in the material.
[0009] α-Silicon carbide and β-silicon carbide can introduce more grain boundaries and phase boundaries. These interfaces can serve as strengthening points of grain boundaries, promote the bonding between grains, and make the fracture mode of ceramic materials more inclined to transgranular fracture, that is, the cracks extend through the interior of the grains, which significantly improves the fracture toughness of ceramic materials.
[0010] The composite additive introduces zirconium and yttrium elements, which are mixed with silicon carbide powder of different phases. They can be adsorbed on the surface of grains or enter the grain boundaries, acting as inhibitors to hinder the further growth of grains and refine the grain structure, thereby preventing excessive growth of grains during solid-phase sintering. It can promote the grain boundary bonding between different phases, enhance the strength and toughness of the phase interface, and make the crack require more energy to pass through the grain boundary during the expansion process, thereby improving the fracture toughness of the material.
[0011] Optionally, the average particle size of the α-silicon carbide is 200-400 nm, and the average particle size of the β-silicon carbide is 50-150 nm.
[0012] Optionally, the carbon source auxiliary agent includes an organic carbon source and an inorganic carbon source in a mass ratio of (1-4):2.
[0013] By adopting the above technical solution, inorganic carbon sources tend to agglomerate easily and are difficult to be evenly dispersed in silicon carbide powder, while the carbon produced by the cracking of organic carbon sources is introduced in the form of organic matter and wrapped on the surface of silicon carbide powder. The cracked carbon has good dispersibility in silicon carbide.
[0014] The mixed use of two carbon sources can utilize the dispersibility advantage of organic carbon to help inorganic carbon be better dispersed in silicon carbide powder, thereby improving the overall dispersion effect of the mixed carbon source, and then effectively inhibiting the excessive growth of grains of silicon carbide powder during solid phase sintering, thereby improving the fracture toughness of silicon carbide ceramics.
[0015] Optionally, the organic carbon source is selected from phenolic resin, and the inorganic carbon source is selected from carbon black powder.
[0016] Optionally, the boron source is selected from boron carbide.
[0017] Optionally, the binder is selected from any one of polyacrylate and polyvinyl alcohol.
[0018] By adopting the above technical solution and selecting a suitable binder, it is helpful to provide sufficient bonding force during the ceramic forming process to ensure the shape stability and integrity of the green blank.
[0019] In a second aspect, the present application provides a method for preparing solid phase sintered silicon carbide ceramics, using the following technical solution: A method for preparing solid phase sintered silicon carbide ceramics comprises the following steps: The fluidized bed chemical vapor deposition method is adopted, the zirconium chloride and yttrium chloride composite additives are placed in the gasification section, the α-silicon carbide powder is placed in the fluidized bed reaction section, and argon gas is introduced into the system to remove the air in the entire system; hydrogen gas with a flow rate of 100-200 mL / min is used as a carrier gas, and the vapor deposition treatment is carried out at 800-900° C. for 1-1.5 hours, the hydrogen gas is turned off, and the modified α-silicon carbide is cooled to obtain; The modified α-silicon carbide, β-silicon carbide, a carbon source additive, a boron source additive, a composite additive, a binder and a solvent are uniformly mixed to obtain a mixed slurry; The mixed slurry is spray-dried and granulated to obtain granulated powder; The granulated powder is isostatically pressed to obtain a green blank of a desired shape; The green blank is sintered in an argon protective atmosphere and then cooled to room temperature in a furnace to obtain a green blank.
[0020] By adopting the above technical solution, α-silicon carbide is a cubic silicon carbide with a more stable crystal structure than β-silicon carbide and a larger lattice constant, which is beneficial to the adsorption and reaction of atoms or molecules on the surface during the vapor deposition process, so that the zirconium chloride and yttrium chloride composite additives can be better attached to the surface of α-silicon carbide to form a uniform coating.
[0021] The α-silicon carbide and β-silicon carbide that have been surface-modified by the composite additive are mixed to form a more optimized grain boundary structure during the sintering process. This is because the composite additive on the surface of α-silicon carbide can promote solid-phase diffusion during solid-phase sintering, thereby forming a stronger bond at the grain boundary and significantly improving the fracture toughness of silicon carbide ceramics.
[0022] Only surface modification of α-silicon carbide can improve the sintering activity of α-silicon carbide, while β-silicon carbide still maintains the finer grain size of the raw material. After mixing, it helps to reduce the excessive growth of grains as a whole and promote the densification of ceramic materials. β-Silicon carbide provides a stable matrix, while modified α-silicon carbide plays a reinforcing role, allowing silicon carbide ceramics to maintain a high fracture toughness.
[0023] Optionally, the specific parameters of the mixed slurry spray drying granulation are: inlet temperature is 160-180°C, and outlet temperature is 60-80°C.
[0024] Optionally, the conditions for sintering the green blank are: First, heat up to 1800-1900℃ at a heating rate of 5-7℃ / min and keep warm for 0.5-1h; Then increase the temperature to 2000-2100°C at a heating rate of 2-4°C / min and keep it at this temperature for 1-1.5h.
[0025] By adopting the above technical solution, through a two-step temperature-controlled sintering method, rapid heating in the low-temperature heat treatment stage helps to suppress the growth rate of silicon carbide grains; in the high-temperature heat treatment stage, slow heating promotes the growth of silicon carbide particles and prevents excessive grain growth at high temperatures.
[0026] By gradually increasing the temperature, the defects inside the material can be released and healed at a lower temperature, thereby reducing the possibility of defect formation at high temperature and improving the yield of silicon carbide ceramics.
[0027] Optionally, the conditions for isostatic pressing of the granulated powder are: pressure 200-250 MPa, and holding time 1-2 min.
[0028] In summary, this application has the following beneficial effects: 1. In the present application, zirconium chloride and yttrium chloride composite additives are deposited on the surface of α-silicon carbide by chemical vapor deposition and then mixed with β-silicon carbide, thereby introducing more grain boundaries and phase boundaries into the material, promoting the bonding between grains, forming a stronger bond at the grain boundary, and effectively controlling the growth of grains during solid phase sintering, making the fracture mode of the ceramic material more inclined to transgranular fracture, and significantly improving the fracture toughness of the ceramic material.
[0029] 2. In the present application, a mixture of an organic carbon source and an inorganic carbon source in a suitable ratio is preferably used as a carbon source additive. The organic carbon source is cracked and introduced into the carbon source in the form of organic matter and is coated on the surface of the silicon carbide powder, which makes up for the dispersibility disadvantage of the inorganic carbon source and improves the overall dispersion effect of the mixed carbon source. It effectively inhibits the excessive growth of grains of silicon carbide powder during solid phase sintering and improves the fracture toughness of silicon carbide ceramics.
[0030] 3. The method of the present application prepares silicon carbide ceramics by solid-phase sintering through spray drying granulation, isostatic pressing and staged sintering, which effectively avoids the defects of the green body caused by the preparation process such as granulation and uneven pressure, optimizes the microstructure of the material, and effectively improves the quality of solid-phase sintered silicon carbide ceramics. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with all the embodiments and comparative examples.
[0032] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: α-Silicon carbide, purity>99.9%, average particle size 200-400nm; β-Silicon carbide, purity>99.9%, average particle size 50-150nm; Zirconium chloride, selected from Jizhi Biochemical Technology, Z53080; Yttrium chloride, selected from Zhiheng Zhiyuan, lhy-1; Carbon black powder, selected from Cabot, N550; Phenolic resin, selected from Yoshida, BF01; Boron carbide, selected from Zhongke Yannuo, BC035251000; Polyacrylate, selected from Square Top, FDC-100; Polyvinyl alcohol, selected from Sichuan Wei, 088-20. Example
[0033] Example 1 A solid-phase sintered silicon carbide ceramic, wherein the amounts of raw materials and raw material components are shown in Table 1, wherein the silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:4.5; the composite additive comprises zirconium chloride and yttrium chloride in a mass ratio of 3:1; the carbon source additive is carbon black powder; the boron source additive is boron carbide powder; and the binder is polyacrylate.
[0034] Table 1 The above-mentioned method for preparing solid phase sintered silicon carbide ceramics comprises the following steps: S1: using a fluidized bed chemical vapor deposition device, the device includes a fluidized bed reactor and a gasifier, placing zirconium chloride and yttrium chloride composite additives in a gasification section, placing α-silicon carbide powder in a fluidized bed reaction section, and introducing excess argon gas into the gasification section to remove air in the entire system; Using hydrogen gas at a flow rate of 200 mL / min as a carrier gas, vapor deposition treatment was performed at 900° C. for 1 h, the hydrogen gas was turned off, and the mixture was cooled to obtain modified α-silicon carbide; S2: uniformly mixing the modified α-silicon carbide, β-silicon carbide, carbon source additive, boron source additive, composite additive and binder with the solvent ethanol at a material-liquid ratio of 1:4 to obtain a mixed slurry; S3: granulating the mixed slurry through a spray drying device to obtain granulated powder, the inlet temperature of the spray drying is 180°C, and the outlet temperature is 80°C; S4: isostatically pressing the granulated powder under a pressure of 250 MPa, holding the pressure for 1 min, to obtain a green blank of the desired shape; S5: In an argon protective atmosphere, the green billet is first heated to 1800° C. at a heating rate of 5° C. / min and kept at this temperature for 1 hour; then heated to 2100° C. at a heating rate of 4° C. / min and kept at this temperature for 1.5 hours, and then cooled to room temperature in the furnace.
[0035] Example 2 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the amounts of the raw materials and the raw material components are as shown in Table 1, wherein the silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:4.5; the composite additive comprises zirconium chloride and yttrium chloride in a mass ratio of 1:1; and the binder is polyvinyl alcohol.
[0036] The preparation method of the solid phase sintered silicon carbide ceramic comprises the following steps: S1: using a fluidized bed chemical vapor deposition device, the device includes a fluidized bed reactor and a gasifier, placing zirconium chloride and yttrium chloride composite additives in a gasification section, placing α-silicon carbide powder in a fluidized bed reaction section, and introducing excess argon gas into the gasification section to remove air in the entire system; Using hydrogen gas at a flow rate of 100 mL / min as a carrier gas, vapor deposition treatment was performed at 800° C. for 1.5 h, the hydrogen gas was turned off, and the mixture was cooled to obtain modified α-silicon carbide; S2: uniformly mixing the modified α-silicon carbide, β-silicon carbide, carbon source additive, boron source additive, composite additive and binder with the solvent ethanol at a material-liquid ratio of 1:4 to obtain a mixed slurry; S3: granulating the mixed slurry through a spray drying device to obtain granulated powder, the inlet temperature of the spray drying is 160°C, and the outlet temperature is 60°C; S4: isostatically pressing the granulated powder under a pressure of 200 MPa, and maintaining the pressure for 2 minutes to obtain a green blank of the desired shape; S5: In an argon protective atmosphere, the green billet is first heated to 1900° C. at a heating rate of 7° C. / min and kept at this temperature for 0.5 h; then heated to 2000° C. at a heating rate of 2° C. / min and kept at this temperature for 1 h, and then cooled to room temperature in the furnace.
[0037] Example 3 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the amounts of the raw materials and the raw material components are as shown in Table 1, wherein the silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:5; and the composite additive comprises zirconium chloride and yttrium chloride in a mass ratio of 4:1.
[0038] The preparation method of the solid phase sintered silicon carbide ceramic comprises the following steps: S1: using a fluidized bed chemical vapor deposition device, the device includes a fluidized bed reactor and a gasifier, placing zirconium chloride and yttrium chloride composite additives in a gasification section, placing α-silicon carbide powder in a fluidized bed reaction section, and introducing excess argon gas into the gasification section to remove air in the entire system; Using hydrogen gas at a flow rate of 200 mL / min as a carrier gas, vapor deposition treatment was performed at 900° C. for 1.5 h, the hydrogen gas was turned off, and the mixture was cooled to obtain modified α-silicon carbide; S2: uniformly mixing the modified α-silicon carbide, β-silicon carbide, carbon source additive, boron source additive, composite additive and binder with the solvent ethanol at a material-liquid ratio of 1:4 to obtain a mixed slurry; S3: granulating the mixed slurry through a spray drying device to obtain granulated powder, the inlet temperature of the spray drying is 170°C, and the outlet temperature is 70°C; S4: isostatically pressing the granulated powder under a pressure of 220 MPa, and maintaining the pressure for 2 minutes to obtain a green blank of the desired shape; S5: In an argon protective atmosphere, the green billet is first heated to 1800° C. at a heating rate of 6° C. / min and kept at this temperature for 1 hour; then heated to 2000° C. at a heating rate of 3° C. / min and kept at this temperature for 1.5 hours, and then cooled to room temperature in the furnace.
[0039] Example 4 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the amounts of the raw materials and the raw material components are as shown in Table 1, wherein the silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:4.7; and the composite additive comprises zirconium chloride and yttrium chloride in a mass ratio of 5:1.
[0040] Example 5 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the carbon source additive is an organic carbon source and an inorganic carbon source in a mass ratio of 1:2, the organic carbon source is phenolic resin, and the inorganic carbon source is carbon black powder, and the other steps are the same as Example 1.
[0041] Example 6 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the carbon source additive is an organic carbon source and an inorganic carbon source in a mass ratio of 1:1, the organic carbon source is phenolic resin, and the inorganic carbon source is carbon black powder, and the other steps are the same as Example 1.
[0042] Example 7 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that the carbon source additive is an organic carbon source and an inorganic carbon source in a mass ratio of 2:1, the organic carbon source is phenolic resin, and the inorganic carbon source is carbon black powder, and the other steps are the same as Example 1.
[0043] Comparative Example Comparative Example 1 A solid phase sintered silicon carbide ceramic, which differs from Example 1 in that no composite additive is used, and other steps are the same as Example 1.
[0044] Comparative Example 2 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that yttrium chloride is not used, the yttrium chloride in the composite additive is replaced by zirconium chloride of equal mass, and the other steps are the same as Example 1.
[0045] Comparative Example 3 A solid-phase sintered silicon carbide ceramic, which differs from Example 1 in that zirconium chloride is not used, the zirconium chloride in the composite additive is replaced by yttrium chloride of equal mass, and the other steps are the same as Example 1.
[0046] Comparative Example 4 A solid phase sintered silicon carbide ceramic, which differs from Example 1 in that the fluidized bed vapor deposition method in step S1 is not performed, and the preparation method thereof comprises the following steps: S1: mixing zirconium chloride and yttrium chloride composite additives, α-silicon carbide, β-silicon carbide, carbon source additives, boron source additives, composite additives and binder with solvent ethanol at a material-liquid ratio of 1:4 to obtain a mixed slurry; S2: granulating the mixed slurry through a spray drying device to obtain granulated powder, the inlet temperature of the spray drying is 180°C, and the outlet temperature is 80°C; S3: isostatically pressing the granulated powder under a pressure of 250 MPa, holding the pressure for 1 min, to obtain a green blank of the desired shape; S4: In an argon protective atmosphere, the green blank is first heated to 1800° C. at a heating rate of 5° C. / min and kept at this temperature for 1 hour; then heated to 2100° C. at a heating rate of 4° C. / min and kept at this temperature for 1.5 hours, and then cooled to room temperature in the furnace.
[0047] Comparative Example 5 A solid phase sintered silicon carbide product, the preparation method of which comprises the following steps: S1: 100 kg of micron-sized silicon carbide powder and 0.3 kg of boron carbide powder were put into a vertical mill and ground using water as a solvent to obtain a slurry with a particle size of 0.4-0.8 μm and a solid content of 45 wt%; S2: Add 1 kg of water-soluble carbon black and 1 kg of binder to the slurry of S1, stir evenly, and use centrifugal spray granulation with an inlet temperature of 225°C and an outlet temperature of 98°C to obtain silicon carbide granulated powder; S3: Take 100 kg of the silicon carbide granulated powder prepared in S2, add it to a mixer, then add 4 kg of plasticizer, start the mixer, mix the two evenly, then add 20 kg of deionized water and 1.5 kg of lubricant, stir evenly, and obtain wet powder; S4: sealing and aging the wet powder at a temperature of 5° C. and a humidity of 40% for 24 hours to obtain an aged material; S5: kneading the stale material at a temperature of 25° C., a pressure of 1.0 MPa, and a vacuum degree of -0.08 MPa for 25 min, and repeatedly kneading the mud 4 times to obtain a kneaded mud material; S6: Extruding the slurry under the conditions of an extrusion pressure of 1.0 MPa, a vacuum degree of -0.08 MPa, and an extrusion rate of 0.5 m / min, and obtaining a blank after synchronous speed measurement and synchronous fixed-length cutting; S7: Directly place the green embryo into a far-infrared dryer with gas suspension for primary drying, with a drying working area length of 4 m, a primary drying temperature of 80° C., and a material conveying speed of 1 m / min; then perform secondary drying in a hot air drying oven, with a secondary drying temperature of 120° C. and a secondary drying time of 20 h, to obtain a dried silicon carbide green embryo; S8: placing the dried silicon carbide blank in a high-temperature resistance furnace and performing heat treatment under the protection of an argon atmosphere, wherein the heat treatment includes debonding treatment, carbon thermal reduction treatment and high-temperature sintering; Debonding treatment: set the temperature of the high-temperature resistance furnace to increase the temperature to 300°C at a rate of 3°C / min, then increase the temperature to 600°C at a rate of 0.6°C / min, and then increase the temperature to 900°C at a rate of 1.5°C / min, and keep it at 900°C for 2 hours; Carbothermal reduction treatment: Carbothermal reduction treatment includes the following steps: continue to increase the temperature to 1400°C at a rate of 2°C / min, then increase the temperature to 1550°C at a rate of 0.5°C / min, and keep it at 1550°C for 2 hours; High temperature sintering: then raise the temperature to 1950°C at a rate of 3°C / min, then raise the temperature to 2100°C at a rate of 1.5°C / min, and keep the temperature at 2100°C for 2.5h to obtain a sintered product; S9: After cutting and finishing the inner and outer round chamfers of the sintered product, a silicon carbide heat exchange tube with an outer diameter of 14 mm and a wall thickness of 1.5 mm is obtained.
[0048] Performance testing The solid phase sintered silicon carbide ceramics obtained in Examples 1-7 and Comparative Examples 1-4 were respectively made into samples of 3 mm×4 mm×36 mm in size. With reference to the detection method in the industry standard JCT2212-2014 "Normal Pressure Solid Phase Sintered Silicon Carbide Ceramic Heat Exchange Tube", the performance of the solid phase sintered silicon carbide ceramic samples prepared in Examples 1-7 and Comparative Examples 1-4 was tested, and the test results are recorded in Table 2.
[0049] Table 2 According to the performance test results in Table 2, it can be seen that the flexural strength of the solid phase sintered silicon carbide ceramics of the present application is between 775-804 MPa, and the fracture toughness is between 8.5-10.2 MPa·m 1 / 2 The Vickers hardness is between 26.6-29.0GPa, and the sintered density is between 3.14-3.2g / cm 3 At a high temperature of 1400°C, the flexural strength of the solid-phase sintered silicon carbide ceramic of the present application is between 626-667MPa. Compared with the solid-phase sintered silicon carbide ceramic product of the prior art in Comparative Example 5, it can be seen that the solid-phase sintered silicon carbide ceramic of the present application has excellent fracture toughness and mechanical properties, and has broad application prospects in the field of high-temperature refractory materials.
[0050] According to the performance test results of Examples 1-4 and Examples 5-7, it can be seen that the mixed use of organic carbon and inorganic carbon as two carbon sources can utilize the dispersibility advantage of organic carbon to help the inorganic carbon to be better dispersed in the silicon carbide powder, thereby improving the overall dispersion effect of the mixed carbon source, and further effectively improving the density, fracture toughness and various mechanical properties of silicon carbide ceramics.
[0051] It can be seen from the performance test results of Examples 1-4 and Comparative Examples 1-4 that the present application adopts zirconium chloride and yttrium chloride composite additives, introduces more grain boundaries and phase boundaries into the material, promotes the bonding between grains, forms stronger bonding at the grain boundaries, and effectively controls the growth of grains during solid phase sintering, making the fracture mode of the ceramic material more inclined to transgranular fracture, thereby significantly improving the fracture toughness of the ceramic material.
[0052] Compared with directly mixing the composite additives with silicon carbide powder, the zirconium chloride and yttrium chloride composite additives are deposited on the surface of α-silicon carbide by chemical vapor deposition and then mixed with β-silicon carbide. This allows the composite additives to adhere better to the surface of silicon carbide powder to form a more uniform and stable coating, thereby enhancing the bonding between grain boundaries and promoting the improvement of the fracture toughness and various mechanical properties of silicon carbide ceramics prepared by solid phase sintering.
[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A solid phase sintered silicon carbide ceramic, characterized in that: According to the mass percentage, the raw materials include 86.5-92.5% of silicon carbide powder, 3-6% of carbon source additive, 0.2-1% of boron source additive, 2-5% of composite additive and 2-5% of binder; The silicon carbide powder comprises α-silicon carbide and β-silicon carbide in a mass ratio of 1:(4.5-5); The composite auxiliary agent includes zirconium chloride and yttrium chloride in a mass ratio of (1-5):
1.
2. The solid phase sintered silicon carbide ceramic according to claim 1, characterized in that: The average particle size of the α-silicon carbide is 200-400 nm, and the average particle size of the β-silicon carbide is 50-150 nm.
3. The solid phase sintered silicon carbide ceramic according to claim 1, characterized in that: The carbon source auxiliary agent comprises an organic carbon source and an inorganic carbon source in a mass ratio of (1-4):
2.
4. The solid phase sintered silicon carbide ceramic according to claim 3, characterized in that: The organic carbon source is selected from phenolic resin, and the inorganic carbon source is selected from carbon black powder.
5. The solid phase sintered silicon carbide ceramic according to claim 1, characterized in that: The boron source is selected from boron carbide.
6. The solid phase sintered silicon carbide ceramic according to claim 1, characterized in that: The binder is selected from any one of polyacrylate and polyvinyl alcohol.
7. A method for preparing a solid phase sintered silicon carbide ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: The fluidized bed chemical vapor deposition method is adopted, the composite additives of zirconium chloride and yttrium chloride are placed in the gasification section, the α-silicon carbide powder is placed in the fluidized bed reaction section, and argon gas is introduced into the system to remove the air in the whole system; Using hydrogen gas at a flow rate of 100-200 mL / min as a carrier gas, performing a vapor deposition treatment at 800-900° C. for 1-1.5 hours, shutting off the hydrogen gas, cooling, and obtaining modified α-silicon carbide; The modified α-silicon carbide, β-silicon carbide, a carbon source additive, a boron source additive, a composite additive, a binder and a solvent are uniformly mixed to obtain a mixed slurry; The mixed slurry is spray-dried and granulated to obtain granulated powder; The granulated powder is isostatically pressed to obtain a green blank of a desired shape; The green blank is sintered in an argon protective atmosphere and then cooled to room temperature in a furnace to obtain a green blank.
8. The method for preparing solid phase sintered silicon carbide ceramics according to claim 7, characterized in that: The specific parameters of the mixed slurry spray drying granulation are: inlet temperature is 160-180°C, and outlet temperature is 60-80°C.
9. The method for preparing solid phase sintered silicon carbide ceramics according to claim 7, characterized in that: The conditions for sintering the green billet are: First, heat up to 1800-1900℃ at a heating rate of 5-7℃ / min and keep warm for 0.5-1h; Then increase the temperature to 2000-2100°C at a heating rate of 2-4°C / min and keep it at this temperature for 1-1.5h.
10. The method for preparing solid phase sintered silicon carbide ceramics according to claim 7, characterized in that: The conditions for isostatic pressing of the granulated powder are: pressure of 200-250 MPa, and holding time of 1-2 min.
Citation Information
Patent Citations
Low-temperature preparation method of zirconium-based ceramic electrolyte membrane for fuel cell
CN108281689A
Silicon carbide ceramic and preparation method thereof, and semiconductor part
CN111004034A
Silicon carbide composite ceramic material as well as preparation method and application thereof
CN117819977A
Silicon carbide ceramic sealing material and preparation method thereof
CN117986021A
Fiber-reinforced silicon carbide composite material and preparation method thereof
CN118047621A